Desempenho de grupo motor gerador alimentado com misturas de óleo residual de frituras e diesel sob cargas variadas - Almeida, Antônio Fabrício de (2016)
The residual oil frying (ORF), when disposed of incorrectly, cause negative impacts on the environment. However, its use as biofuel, generates great benefits of social, economic and environmental order. The objective of this study was to evaluate the performance of a group cycle diesel engine-generator powered by diesel and mineral diesel blends with residual oil frying. The trials were conducted in machines Instrumentation Laboratory and Agricultural Mechanization (Limma) of the Federal Rural University of the Semi-Arid (UFERSA) in Mossoró-RN, using a completely randomized design in factorial 4 x 5, with four replications. The treatments were diesel (DI) of oil and mixtures of diesel and residual oil frying (ORF) in the proportions: 50% DI and 50% ORF; DI 75% and 25% ORF; DI 90% and 10% ORF; 100% DI. The resistive loads used were 3, 6, 9, 12 and 15 kW. The engine oil temperature remains within the recommended operating range (85-95 ° C), indicating no lubricating oil contamination. All mixtures ORF had lower values for the exhaust temperature to the commercial diesel. The lower values of specific fuel consumption (EC) were obtained with higher loads, particularly at loads of 12 and 15 kW. The ORF25 mixture was the one with the lowest power generated and the EC farther diesel for all applied loads. Among the binary mixtures, ORF presented SE 10 similar to diesel in loads of 12 and 15 kW and the ORF50, the loads of 3, 9 and 12 kW; demonstrating that such mixing proportions, the ORF can replace mineral diesel